A systematic review of the concentration of potentially toxic elements in fish from the Persian Gulf: A health risk assessment study. (May 2022) - Raissy, Mehdi; Ansari, Mahsa; Chaleshtori, Reza Sharafati; Mahdavi, Vahideh; Hadian, Zahra; Lorenzo, José Manuel; Oliveri Conti, Gea; Huseyn, Elcin; Mousavi Khaneghah, Amin
Abstract: Fish as a critical food source is responsible for supplying nearly 20% of the average per capita animal protein for 3.2 billion people worldwide. However, oral exposure to potentially toxic elements (PTE) such as mercury (Hg), cadmium (Cd), lead (Pb), and arsenic (As) through marine fish consumption can cause health risks in consumers. This study aimed to collect information among databases (2000–2020), including ScienceDirect, PubMed, SCOPUS, EMBASE, and Google Scholar, regarding the concentration of PTEs in different types of fish from the Persian Gulf. In this regard, thirty articles containing 266 samples were included in the current systematic review. In addition, the non-carcinogenic risk caused by ingestion of PTEs via consumption of fish was calculated. The average PTE concentrations in fish muscles were presented in the following order: As (0.37 mg/kg ww) > Pb (0.20 mg/kg ww) > Cd (0.17 mg/kg ww) > Hg (0.13 mg/kg ww). However, the mean concentration of PTEs was below the defined level by the World Health Organization, and the findings revealed that the calculated average daily dose (ADD) for Cd and Pb in Iranian children and adult consumers was lower than the reference dose (RfD), whereas the ADD of Hg was higher than the RfD for children consumers. The total target hazard quotient for Iranian and children consumers was >1. The excess lifetime cancer risk values for Pb were safe, unlike those for Cd, which were in an unsafe range (>10 −4 ) for consumers. Highlights: Data obtained from 30 articles with 266 samples were surveyed. The mean concentrations of potentially toxic elements were lower than the limits recommended. The non-carcinogenic risk for global children's exposure to mercury was unsafe level. Unlike Cd, the cancer risk of Pb was at the safe level for all consumers.